MRI Findings in Pediatric Abusive Head Trauma: A Review. Issue 1 (6th November 2019) - Orman, Gunes; Kralik, Stephen F.; Meoded, Avner; Desai, Nilesh; Risen, Sarah; Huisman, Thierry A.G.M.
ABSTRACT: Trauma is the most common cause of death and significant morbidity in childhood; abusive head trauma (AHT) is a prominent cause of significant morbidity and mortality in children younger than 2 years old. Correctly diagnosing AHT is challenging both clinically and radiologically. The primary diagnostic challenges are that the abused children are usually too young to provide an adequate history, perpetrators are unlikely to provide truthful account of trauma, and clinicians may be biased in their assessment of potentially abused children. The main radiological challenge is that there is no single imaging finding that is independently specific for or diagnostic of AHT. The radiological evaluation should be based on the multiplicity and severity of findings and an inconsistency with the provided mechanism of trauma. While the most common neuroimaging finding in AHT is subdural hemorrhage, other less well‐known magnetic resonance imaging (MRI) findings such as the "lollipop sign" or "tadpole sign, " parenchymal or cortical lacerations, subpial hemorrhage, cranio‐cervical junction injuries including retroclival hematomas, as well as diffuse hypoxic brain injury have been identified and described in the recent literature. While AHT is ultimately a clinical diagnosis combining history, exam, and neuroimaging, familiarity with the typical as well as the less‐well known MRI findings will improve recognition of AHT by radiologists.